"Backing Weakness:" Conceptualizations of Q'eqchi' Women's Vulnerability in Belize. Issue 5 (4th July 2022) - Waldram, James B.
ABSTRACT: Q'eqchi' women's health is the product of inherent, acquired, and induced vulnerabilities that inform an idiom of "weakness" characteristic of women compared to men, reflecting both biological difference and gender-specific demands placed upon them within the context of village life. While women are understood to be uniquely vulnerable to sickness – their "weakness" – they demonstrate great strength and vigor to perform culturally prescribed roles, such as "backing" heavy loads. A framework grounded in Indigenous culture and ideology interprets Q'eqchi' understandings of women's health and broader position within society, arguing the need to take seriously Indigenous explanatory frameworks.